Investigating medicinal plants for antimicrobial benefits in a changing climate - Ali Yetgin (International Journal of Secondary Metabolite)
As the world's climate changes, there is growing concern about how it is affecting human health, including the rise of antimicrobial resistance. Medicinal plants have been used for centuries and their antimicrobial properties have been recognized by many cultures. This article focuses on exploring the potential of medicinal plants for antimicrobial activity in the face of climate change challenges. The article discusses the challenges and opportunities associated with using medicinal plants as a source of new antimicrobial agents, including issues related to the changes in plant chemistry caused by climate change, and the need for sustainable and ethical sourcing practices. The article also examines the importance of traditional knowledge and cultural practices in the development and conservation of medicinal plants. Finally, the article highlights the importance of interdisciplinary research and collaboration in harnessing the potential of medicinal plants for combating antimicrobial resistance in the context of a changing climate.